EFFECTIVENESS OF ACTIVE LEARNING STRATEGY OF GIVING QUESTION AND GETTING ANSWERS AND INDEX CARD MATCH LEARNING TOWARDS LEARNING OUTCOMES IN MATHEMATICS STUDENTS - Mei Astuti; Abdul Taram (Universitas Ahmad Dahlan, 2018)
The strategies used in the teaching and learning process are still fixed on speech and discussions, so the result of student learning interest is low. Strategies that can be used to increase student’s interest in learning among them is Giving Question And Getting Answer (GIGA) and Index Card Match (ICM). GIGA is one of the active learning strategies to ask a question and receive a good answer used to involve students in repeating learning materials that have been delivered. ICM is an active learning strategy looking for a pleasant enough partner used to repeating learning materials that have been given before. This research aims to determine the effectiveness of mathematics learning by using strategy Giving Question And Getting Answer compared with Index Card Match strategy on mathematical learning outcomes students class XI IPS SMA Muhammadiyah 3 Yogyakarta in the second semester of the academic year 2016/2017. The design of this research is a posttest only control design. This research population is the student's class XI IPS Senior High School of Muhammadiyah 3 Yogyakarta. Sample in this research was taken using simple random sampling obtained class XI IPS 2 as experiment class A and class XI IPS 1 as experiment class B. Data collection is done by a test method. Instrument testing uses validity and reliability. The data analysis technique using a prerequisite analysis test includes the normality test with the Chi-square formula, homogeneity test with Bartlett test, and hypothesis test with t-test. The results of the study are significant a=5%, and df=69 obtained the conclusion that : (1) There are differences in the results of learning mathematics students learning using the strategy of active learning Giving Question and Getting Answer with learning using strategy of active learning type Index Card Match. This is indicated by the results of the first hypothesis test that tcount =2,0318 > ttabel = 1,9949. (2) Learning using strategy of active learning type Giving Question And Getting Answer more effective than learning using the active learning strategy of Index Card Match type. This is shown from the result of the second hypothesis test that tcount=2,0318> ttabel=1,6672.